Compensating expatriates in Polish subsidiaries – pilot research findings - Przytuła, Sylwia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This article, of a theoretical-empirical nature, presents the practices of compensating expatriates working in Poland. The first part of the article is devoted to the research findings concerning compensation practices by foreign authors, and on this basis the practices in Polish subsidiaries are presented. The pilot research findings, conducted on 105 expatriates, show that the most often offered approach to compensating expats is the balance sheet approach, which is also the most popular in other studies. The biggest problems related to compensation are exchange rates and double taxation. Most expats pay taxes in Poland. Besides the base pay, they are offered relocation allowance and education allowance
Argumenta Oeconomica, 2013, Nr 1 (30), s. 149-172
Keywords: expatriate; balance sheet approach; compensation system; mobility premium; relocation allowance; education allowance